Inter Individual Variation and Factors Regulating the Formation of Phosphatidylethanol. (27th September 2019) - Stenton, Joanna; Walther, Lisa; Hansson, Therese; Andersson, Anders; Isaksson, Anders
Abstract : Background: Alcohol use disorders are a major but often unrecognized health problem. Alcohol markers can therefore be of great value for diagnosis, follow‐up, and treatment evaluation. Phosphatidylethanol in blood (B‐PEth) is an alcohol biomarker with higher clinical sensitivity and specificity than commonly used alcohol markers but has shown a considerable interindividual variation in relation to reported consumption. Methods: An in vitro system was used to investigate factors, which may affect the formation rate of PEth or which may give rise to interindividual variation in the rate of formation. In this system, isolated erythrocytes from 31 individuals were incubated in the presence of various concentrations of ethanol (EtOH). The concentration of PEth and phosphatidylcholine (PC), the parent molecule of PEth, was determined by chromatographic methods. Results: Time, EtOH, and PC concentration were major factors determining the amount of PEth formed. The interindividual variation in PEth formation rate, calculated at an EtOH concentration of 50 mmol/l, showed a coefficient of variation (CV) from 23 to 31% for the different PEth forms studied (PEth 16:0/18:2, total PEth and PEth 16:0/18:1). The concentration of PC was found to be an important determinant of this variation. The formation rate for PEth 16:0/18:2 was somewhat higher than for PEth 16:0/18:1. The formation of PEth 16:0/18:1 but not PEth 16:0/18:2 showed a positive correlation to the concentration of PEth at baseline (endogenous PEth). Calculation of enzyme kinetics for the reaction resulting in the formation of PEth 16:0/18:1 or PEth 16:0/18:2 showed an apparent K m (Michaelis constant) of approximately 160 to 170 mmol/l. Conclusions: Interindividual variation in the formation rate of PEth appears to be a significant but relatively modest source of variation in the relation between B‐PEth and reported consumption. Correction for interindividual variation in PC concentrations might substantially reduce the interindividual variability in PEth formation and consequently in B‐PEth. Abstract : Phosphatidylethanol in blood (B‐PEth) is a direct alcohol use biomarker with higher clinical sensitivity and specificity than commonly used markers. B‐PEth correlates to reported alcohol consumption although with distinct interindividual variation. Results presented here show that interindividual variation in the formation rate of PEth is a significant but rather modest source of this variation. Furthermore, interindividual differences in the formation rate could to a large extent be explained by differences in the concentration of phosphatidylcholine, the parent molecule of PEth.